(untitled) (Baghdad Science Journal, 2021)
Antibacterial activity of CNSs against Staphylococcus aureus and Escherichia coli was estimated. Higher inhibition zone of 18 mm and 20 mm were observed against S. aureus and E.coli, respectively, at a concentration of 2 mg/ml of carbon nanosphere after 24 hrs of incubation at 37 ºC. In vitro cytotoxicity experiment was performed on two parasite strains of Leishmania donovani and Leishmania tropica by using MTT assay. L. donovani revealed more sensitiv to the CNSs than L. tropica. An intermediate level of cytotoxicity of 51.31 % was observed when 2.4 mg/ml of CNSs was incubated with L. donovani, while weak cytotoxicity of 37.20 % was shown when the same concentration of CNSs was used against L. tropica within 24 hr at 37 ºC.